Demon and Hero: Mani Ratnam's Raavanan and de-mythologising the Indian discourse of the nation - Ahmad, Siti Nuraishah (2015)
The epic poem Ramayana occupies a central position in the religious, social and cultural lives of peoples in the Indian subcontinent, as well as in regions elsewhere in Asia that have had contact with the poem. Narratives and characters found in the Ramayana have also been incorporated in the discourse of the modern Indian nation-state and the construction of a national identity through recitation, performance and adaptation into various cultural forms, in what Benedict Anderson (2006) calls acts of imagining the nation. But what happens when one takes a founding myth like the Ramayana as a means of challenging present-day India’s discourse of the nation? Mani Ratnam’s film adaptation of the epic, Raavanan (2010) is an attempt at re-appropriating and revising the core narrative and characters of the Ramayana in order to draw attention to the limitations of the Indian nation-state, particularly in its treatment of subaltern communities (peasants, indigenous people) and use of state-sanctioned violence against dissent. Using postcolonial critiques of the nation and nationalism, this paper will examine how Raavanan reveals the faultlines in the Indian nation-state’s self-fashioning of itself as a modern, progressive political entity by thrusting the demonized Other (Ravana) into the centre of the narrative, as well as re-casting its female characters i.e. Sita and Surpanakha (Ravana’s sister).